Effect of the initial glucose concentration on the performance of ice wine fermentation of Vidal grape juice - Ye Zhang; Chun Hao Chang; Xue Hai Fan; Ting Ting Zuo; Ziwei Jiao (Scientific Reports)
Abstract Ice wine is produced from concentrated grape juice obtained by the natural freezing and pressing of grapes. The high sugar content of this juice has an impact on fermentation. To investigate the impact of the initial sugar concentration on the fermentation of ice wine, the initial sugar concentration of Vidal ice grape juice was adjusted to 370, 450, 500 and 550 g/L by the addition of glucose. The fermentation process was conducted at a temperature of 18 °C with Zymaflore ST yeast. To ensure optimal fermentation, the yeast assimilable nitrogen (YAN) in the grape juice was adjusted to 350 mg/L using a commercial nitrogen source. The initial sugar concentrations (370, 450, 500, and 550 g/L) were significantly negatively correlated with the number of viable yeast during active fermentation, the total consumption of sugar and YAN, and ethanol production (130.26, 117.83, 106.14, and 90.85 g/L) but positively correlated with the production of acetic acid (0.82–2.86 g/L) and acetaldehyde. Fermentation with initial sugar concentrations ≥ 500 g/L (500 and 550 g/L) produced ethanol (106.14 and 90.85 g/L) and excessive acetic acid (2.14 and 2.86 g/L), inhibited the esterification of n-butanol and n-hexanol, and promoted the production of isopentanol, isoamyl acetate, diethyl succinate, ethyl hexanoate and ethyl octanoate while increasing the production of 2-phenylethanol and isobutanol. The initial sugar concentration affected the production of glycerol, isobutanol, ethyl acetate, and diethyl succinate, but it did not affect the final contents of the ice wine. This study examined fermentation dynamics, including substrate consumption, yeast cell production, and the production of important metabolites such as ethanol, acetic acid, higher alcohols, and esters. Appropriate initial concentrations of YAN and sugar (below 500 g/L) and a relatively high ratio of glucose to fructose (between 1:1 and 1.7:1) is preferable for effective ice wine fermentation.